The Wiley-Blackwell handbook of family psychology - Bray, James H.; Stanton, Mark (Wiley-Blackwell, 2009)
Provides a comprehensive overview of the range of disciplines relating to family psychology - a field that transcends the treatment of families to include psychological services to individuals, couples, and large organizations based on the tenets of systems theory and the science of family psychology